Off-on fluorescence monitoring of intracellular Ag+ in single living cells using an Ag+-responsive probe. (23rd October 2017) - Lv, Jian; Zhao, Li-Jun; Qian, Ruo-Can; Long, Yi-Tao
Abstract: Detection of silver ions (Ag + ) in living cells has becoming more and more attractive due to the important biological impact of Ag + on cellular functions. Here, we put forward a new approach to realize the in situ fluorescence imaging and detection of Ag + in single cells via an ultrasensitive Ag + -responsive probe, 3′, 6′-bis (diethylamino)-2-(2-iodoethyl) spiro[isoindoline-1, 9′-xanthen]-3-one (BDISIX). In the presence of Ag +, the fluorescence of the probe can be turned 'on', generating strong red fluorescence. Using breast cancer cells (MCF-7) as the example, we successfully realize the imaging of intracellular Ag + through one-step incubation of the probe, which is especially convenient and fast for the in situ intact detection of Ag + in living cells.